ATTENTION TO POTTERY ART IN ANDIJAN REGION DURING THE YEARS OF INDEPENDENCE - Umarov Hasanboy Yo‘ldoshevich (Journals Park Publishing, 2024)
Medium Asia in the area of pottery development stages and pottery addresses data given Pottery schools, especially Rishton pottery traditions applied decoration types.